Reactive oxygen species production by quercetin causes the death of Leishmania amazonensis intracellular amastigotes - Silva, Fernanda Fonseca (2013)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Bioquímica de Tripanosomatideos. Rio de Janeiro, RJ. Brasil.